Electrochemical Reaction of Sm(III) on Liquid Sn Electrode. Issue 2 (9th January 2020) - Li, Mei; Sun, Zhongxuan; Han, Wei; Sun, Yang; Yang, Xiaoguang; Wang, Wei
Abstract : The electrochemical study of Sm(III) ions was conducted on Sn film electrode in eutectic LiCl-KCl in the temperature range from 773 K to 923 K by a series of electrochemical techniques. The results of current reversal chronopotentiometry of Sm(III) on W electrode showed that the redox reaction related to Sm(III) is a kind of soluble/soluble system, which meant that Sm(III) was reduced to Sm(II) on W electrode. On Sn film electrode, the reduction of Sm(III) was found to be two-step process: Sm ( III ) + e ‒ = Sm ( II ) ; Sm ( II ) + 2e ‒ + xSn = SmSn x . Linear polarization (LP) and Tafel techniques were conducted to measure the exchange current density ( j 0 ) of Sm(II)/SmSn3 couple. The variation of j 0 with temperature accords with the Arrhenius law, and the activation energy was evaluated to be 14.32 kJ mol −1 and 14.08 kJ mol −1, respectively. Moreover, the feasibility of extracting Sm on Sn film electrode was examined by constant potential electrolysis at −1.45 V in the LiCl-KCl-SmCl3 -SnCl2 molten salt for 3 h. XRD result indicated the formation of SmSn3 . Constant current and potential electrolysis were performed to extract metallic Sm on liquid Sn pool electrode. The alloy samples were characterized by SEM-EDS and XRD, which displayed the existence of SmSn3 and Sm4 Sn3 phases in Sm-Sn alloys.